Biogeochemical dynamics of dissolved organic matter in the Changjiang Estuary during a late flooding season - Li, Zhongqiao; Zhao, Ruoshi; Ma, Xiao; Wang, Xiaona; Su, Liang; Li, Hongliang; Jin, Haiyan; Zeng, Jiangning; Chen, Jianfang (Frontiers in Marine Science, 2025)
To address the knowledge gap concerning the behavioral dynamics of dissolved organic matter (DOM) in the Changjiang Estuary during the late flooding season, we conducted an extensive sampling campaign during which 188 water samples were systematically collected across the estuary from August 15th to September 4th, 2021. Through analysis of dissolved organic carbon (DOC) concentrations and optical properties, this study aimed to elucidate the spatial distribution patterns and biogeochemical transformations of DOM during estuarine mixing processes in the late flooding season of the Changjiang. DOC in our study ranged from 0.72 to 2.24 mg/L, with a mean (± standard deviation) of 1.15 ± 0.32 mg/L. The correlation with salinity clearly indicated the dual control of hydrodynamic mixing processes and localized organic matter inputs on DOM abundance. Spectroscopic characterization combined with PARAFAC modeling revealed the predominantly terrestrial signature of chromophoric DOM (CDOM) and its progressive transformation along the estuarine gradient. Notably, rapid consumption of protein-like fluorescent DOM (FDOM) was observed within the Changjiang Estuary’s low-salinity transition zone. The consistent decrease in DOM aromaticity (SUVA254 decline of 0.13 L·mg C-1·m-1 per salinity unit, r2 = 0.77) coupled with increasing spectral slope S275-295 (an increase of 0.0006 nm-1 per salinity unit) clearly demonstrates selective removal of terrestrial constituents, and molecular weight reduction through estuarine processing. These results demonstrate that photochemical degradation might dominate CDOM removal in the Changjiang Estuary.